(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-158-167 Abstract. The relevance of the research problem is due to the need to establish the methodological foundations of modern methods of teaching the Russian language as an independent field of scientific knowledge, the vectors of its development. The author focuses on the analysis of the axiological approach created by A.D.Deikina. The purpose of the article is to determine the potential of axiological linguometrics, to clarify its philosophical, psychological, didactic and methodological foundations. The use of theoretical methods in the study allowed us to establish the following: 1) the axiological approach is the basic category of the methodology – the meta-approach; 2) "Russian (native) language is value" is the essence of an axiological constant; 3) axiological linguometrics, being a strategic direction, a meta–approach, has a significant impact on the development of various vectors of scientific knowledge based on the axiological constant. The article proves the dominant position of the axiological approach in a number of existing approaches, on the basis of which a personality develops and its value orientation, meta-subject and subject skills are formed. Key words: Russian language, methodology, axiological approach, constant, personality, value, value orientation